Ablative Radiotherapy Doses for Locally Advanced: Pancreatic Cancer (LAPC). Issue 6 (November 2017) - Crane, Christopher H.; O'Reilly, Eileen M.
Abstract : Abstract: Standard palliative doses of radiation for locally advanced unresectable pancreatic cancer have had minimal to no impact on survival. Randomized trials evaluating these palliative doses have not shown a significant survival benefit with the use of radiation as consolidation after chemotherapy. Results from nonrandomized studies of 3- to 5-fraction low-dose stereotactic radiation (SBRT) have likewise had a minimal impact, but with less toxicity and a shorter treatment time. Doses of SBRT have been reduced to half the level that is necessary (biological equivalent dose, BED of 53 Gy) to achieve tumor ablation in the treatment of other solid tumors (100 Gy BED) to protect the gastrointestinal (GI) tract. The survival benefit of these palliative options is modest. In contrast, ablative doses of radiation (100 Gy BED) can be delivered using the same SBRT technique in 15 to 25 fractions. In addition to precision tumor targeting and solutions for respiratory motion as with SBRT, the delivery of ablative doses takes advantage of heterogeneous dosing, increased fractionation, which allows higher doses to be given, as well as adaptive planning to address day-to-day GI tract motion in selected cases. These higher doses have resulted in encouraging long-term survival results in multiple studies. In this review, we discuss the critical concepts and components of techniques that can be used to deliver ablative radiotherapy doses for patients with pancreatic tumors: fractionation, intentional dose heterogeneity, respiratory gating, image guidance, and adaptive planning.